2017
DOI: 10.1002/chem.201702629
|View full text |Cite
|
Sign up to set email alerts
|

From a Diphosphanegermylene to Nickel, Palladium, and Platinum Complexes Containing Germyl PGeP Pincer Ligands

Abstract: The PGeP pincer-type germylene Ge(NCH PtBu )C H (1) has been used to prepare a family of group 10 metal complexes, namely, [MCl{κ P,Ge,P-GeCl(NCH PtBu ) C H }] (M=Ni (2 ), Pd (2 ), Pt (2 )), featuring a chloridogermyl PGeP pincer ligand and a Cl-Ge-M-Cl bond sequence. Their reactivity is not initially centered on the metal atom but on their Ge atom. Complexes 2 and 2 easily led to the hydrolyzed products [Ni Cl {μ-(κ P,Ge,P-Ge(NCH PtBu ) C H ) O}], which features a Cl-Ni-Ge-O-Ge-Ni-Cl bond sequence, and [PdCl{… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 70 publications
2
36
0
Order By: Relevance
“…Regarding metal-free PGeP pincer-type germylenes,o nly two specimens have so far been reported, namely,G e-(NCH 2 PtBu 2 ) 2 C 6 H 4 [11] and Ge(NC 6 H 4 PPh 2 ) 2 C 2 H 4 [12] (compounds A and B in Figure 1) and their transition-metal derivative chemistry has just started to be developed. [12][13][14] Both A and B are very prone to get their Ge atom inserted into MÀCl bonds to give chloridogermyld erivatives. It shouldb en oted that Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding metal-free PGeP pincer-type germylenes,o nly two specimens have so far been reported, namely,G e-(NCH 2 PtBu 2 ) 2 C 6 H 4 [11] and Ge(NC 6 H 4 PPh 2 ) 2 C 2 H 4 [12] (compounds A and B in Figure 1) and their transition-metal derivative chemistry has just started to be developed. [12][13][14] Both A and B are very prone to get their Ge atom inserted into MÀCl bonds to give chloridogermyld erivatives. It shouldb en oted that Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated the reaction of the η 2 ‐(Ge–H)Pd 0 4 with ethylene to evaluate the activity for hydrometallation/β‐hydrogen elimination through non‐innocent behavior of the germyl ligand as seen in the Si‐analogue 1 . When the reaction of 4 with 1 atm ethylene was monitored by 1 H and 31 P NMR in [D 8 ]THF, the reaction started at –40 °C to give an ethylpalladium(II) complex 6 bearing a PGeP‐pincer type germyl ligand in 66 % yield after 20 min (Entry 1, Table ) The reaction almost completed within 20 min after the temperature was raised to –20 °C. We previously reported that the hydrometallation of the Si‐analogue 1 under the same reaction conditions occurred at –20 °C to give the ethylpalladium(II) 2 in 40 % yield after 20 min, and 1 was mostly converted to 2 at 0 °C after 30 min .…”
Section: Resultsmentioning
confidence: 99%
“…The reactions of germylene XXV with dichlorido complexes of group 10 metals containing easily displaceable ligands gave the isostructural complexes [MCl{κ 3 P,Ge,P ‐GeCl(NCH 2 P t Bu 2 ) 2 C 6 H 4 }] (M = Ni ( 4 ), Pd ( 5 ), Pt ( 6 ); Figure13), which feature a chloridogermyl PGeP pincer ligand and a Cl–Ge–M–Cl bond sequence . While their Ge atoms are in a tetrahedral environment, their M atoms present a very distorted square plane coordination (P–M–P angles close to 150°) owing to the strain imposed by the short length of the CH 2 P t Bu 2 arms of the pincer ligand.…”
Section: Pep Pincers With 2‐germa‐ and 2‐stannabenzimidazol‐2‐ylidmentioning
confidence: 99%
“…Their reactivity is not initially centered on the metal atom but on their Ge atom. While the platinum complex 6 was reluctant to undergo hydrolysis, complexes 4 and 5 easily led to the hydrolyzed products [Ni 2 Cl 2 {µ‐(κ 3 P , Ge , P ‐Ge(NCH 2 P t Bu 2 ) 2 C 6 H 4 ) 2 O}] ( 9 ), which features a Cl–Ni–Ge–O–Ge–Ni–Cl bond sequence, and [PdCl{κ 3 P , Ge , P ‐Ge(OH)(NCH 2 P t Bu 2 ) 2 C 6 H 4 }] ( 10 ), which contains a hydroxidogermyl PGeP pincer ligand (Figure ) . Chloride exchange reactions (studied with compounds 5 and 6 ) led to the methoxidogermyl, methylgermyl and phenylgermyl derivatives [MCl{κ 3 P , Ge , P ‐GeR(NCH 2 P t Bu 2 ) 2 C 6 H 4 }] (M = Pd, Pt; R = OMe, Me, Ph; compounds 11 – 16 in Figure ).…”
Section: Pep Pincers With 2‐germa‐ and 2‐stannabenzimidazol‐2‐ylidmentioning
confidence: 99%
See 1 more Smart Citation